2007
DOI: 10.1007/s10750-007-9048-7
|View full text |Cite
|
Sign up to set email alerts
|

How well do single samples reflect rotifer species diversity? A test based on interannual variation of rotifer communities in Big Bend National Park (Texas, USA)

Abstract: Studies of rotifer community composition and dynamics often rely on limited sampling regimes.To determine how well species richness is reflected in these studies, we examined interannual variation of rotifer species richness and monogonont community structure from 10 aquatic systems comprising four habitat types-springs, rock pools (tinajas), former cattle tanks, and artificial ponds-in Big Bend National Park (Texas, USA). Planktonic, littoral, and benthic samples were collected from all sites at about the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…Such a reorganised phenomenon at regional level may hint towards a Complex Adaptive System within the metacommunity (Figure 1). Walsh et al (2007) found surprisingly high species richness in the arid ephemeral pond systems which fits our finding about Site 2 exhibiting substantial zooplankton richness, although being temporary in nature. Wallace (2002) opined that rotiferan species abundance can differ markedly and unfortunately, even short term sampling schedules can miss the details of population peaks.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Such a reorganised phenomenon at regional level may hint towards a Complex Adaptive System within the metacommunity (Figure 1). Walsh et al (2007) found surprisingly high species richness in the arid ephemeral pond systems which fits our finding about Site 2 exhibiting substantial zooplankton richness, although being temporary in nature. Wallace (2002) opined that rotiferan species abundance can differ markedly and unfortunately, even short term sampling schedules can miss the details of population peaks.…”
Section: Discussionsupporting
confidence: 90%
“…Values of "j" were mostly high for pairwise combinations of the sub-sites belonging to the Site 1 during monsoon and pre-monsoon in contrast to those during post-monsoon. Walsh et al (2007) (Jurine, 1820) MnB composition of G-II showed maximum similarity with G-PB during monsoon (C N = 0.582) due to overflow, in contrast to post monsoon, when connectivity was disrupted. This suggests that simple connectivity may render similar species assimilations for nearest subsites only and is not sufficient to homogenise the composition of entire water body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species composition is highly affected by sampling site for continental zooplankton (Shaw & Kelso 1992;Walsh et al 2007). Samples within the same water body generally tend to be more similar to each other than samples between water bodies.…”
Section: Species Compositionmentioning
confidence: 99%
“…These metrics have also been used extensively in freshwater systems (Dumont & Segers, 1996;Arnott et al, 1998;Muirhead et al, 2006;Walsh et al, 2007;Kuczyńska-Kippen, 2007). However, few studies have explored biodiversity variation at different temporal and spatial scales (but see Arnott et al, 1998).…”
Section: Introductionmentioning
confidence: 99%